(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Isotonic preparations (beverages) that are currently popular among military personnel and military athletes are beneficial for physical exertion, intense sweating, an active lifestyle, and loss of fluid (for example, in heat). In the market of sports nutrition, isotonic agents are produced in several forms, such as beverages, gels, powders, and tablets. Some will need to be diluted in a ready-made form, while others will need to be diluted according to the instructions attached. To achieve the desired result, it is recommended to follow the general rules of isotonic acceptance. These rules include taking the drug 20 minutes before physical exertion, mainly during training - taking several drinks at intervals between exercises, and paying attention to a person’s individual needs and thirst when determining the necessary amount of the drink. It is important to weigh before and after training to determine the need for the drug and the individual norm. The difference between the weights is the amount of liquid lost, which must be filled. This remedy can be taken after physical exertion, but it is much less helpful. It is better to drink regular water during this period.